Evaluation on the urban green space layout in the central city of Yuxi based on big data - Zhou, Jing; Yang, Maoxiao; Chai, Jing; Wu, Li (Frontiers in Environmental Science, 2022)
As an important part of urban public infrastructure, urban green space plays an indispensable role in urban development and public physical, mental, and emotional health. By collecting open data such as POI, OSM, and ASTER GDEM and using spatial analysis software such as ARCGIS, QGIS, and Global Mapper, this study conducted thermal analysis of crowd activities, service pressure analysis, and demand evaluation for the layout of park green space in the central urban area of Yuxi City. The results show that there are great differences in the area and spatial layout of the thermal classes of crowd activity. Class II occupies the largest area, accounting for 60.73%, while class V occupies the least area, accounting for 2.04%. The thermal classes of crowd activity decrease from the center of the city to the periphery, and their area increases with the decrease of the thermal classes. With the increase in the level of green space service pressure, the proportion of the area decreased, among which the proportion of grade I was as high as 53.20%, while that of grade V was only 1.89%, which was mainly affected by the spatial location. The demand level and the area of park green space are obviously different, mainly concentrated in the first level, accounting for 69.68% of the total demand, and the large area is scattered in the periphery of the central urban area, followed by the fourth level, accounting for 10.46%. The area of other levels, especially the high level of demand, is less. Comprehensive analysis shows that the service level, type of green space, service pressure, and demand of green space have a strong correlation with the geographical location. In future planning, Yuxi City should combine the population distribution density and land development intensity and carry out reasonable layout and planning of park green space by reducing the low-demand area, increasing the green space area of high-demand area, improving public transportation, and improving accessibility.